Analysis of Ecuador's SCOPUS scientific production during the 2001–2020 period by means of standardized citation indicators. Issue 4 (April 2022) - Rodríguez, V.; Flores-Sanchez, M.; Zambrano, C.H.; Rincón, L.; Paz, J.L.; Torres, F.J.
Abstract: An analysis of the scientific production of Ecuador is performed by means of the composite indicator computed for Ecuador-based authors as compared to their counterparts of other South American countries. The dataset employed was obtained from the Databricks platform of the ELSEVIER's International Center for Science Research, ICSR. Therefore, this analysis is limited to the metadata of the documents published in journals indexed in SCOPUS. Comparison of the results obtained for two decades: 2001–2010 and 2011–2020 showed that the number of Ecuador-based researchers has significantly increased in different areas of knowledge. Moreover, comparison between the total number of authors that worked in Ecuador at any given year of the 2011–2020 period and the number of authors that are still working in this country up to the date of the data extraction (i.e., June 2021) showed an average of ∼68% of permanency. Analysis of the percentage distribution in terms of range quarters of the composite indicator (i.e., Q4: 0–1.5, Q3: 1.5–3.0, Q2: 3.0–4.5, and Q1: 4.5–6.0) showed that nearly the totality of the Ecuador-based researchers has composite indicators that lay in the Q4 and Q3 ranges for all the scientific fields considered. The latter was observed to be an effect of the scientific impact of South American countries, with larger investments in science and technology in comparison to Ecuador (i.e., Argentina, Brazil, and Chile). Exclusion of this group of countries in the calculation of the composite indicator of Ecuador-based authors resulted in a noticeable increment of scientists with composite indicators within Q2. Finally, our results suggest, in agreement with previous studies, a correlation between the sustained growth of scientific productivity in the decade 2011–2020 with the scientific programs and policies created by the state, where the initiative of scientific culture is shown as a strategy for growth and development. Abstract : Composite indicator, Ecuador, Science, Technology, and innovation, ICSR.